2019
DOI: 10.2174/1566524019666191001114941
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Nano-biosensors as Novel Approach for the Detection of Lung Cancer-related MicroRNAs

Abstract: In both men and women around the world, lung cancer accounts as the principal cause of cancer-related death after breast cancer. Therefore, early detection of the disease is a cardinal step in improving prognosis and survival of patients. Today, the newly-defined microRNAs regulate about 30 to 60 percent of the gene expression. Changes in microRNA Profiles are linked to numerous health conditions, making them sophisticated biomarkers for timely, if not early, detection of cancer. Though evaluation of microRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 185 publications
0
14
0
Order By: Relevance
“…miRNAs play vital roles in regulating the expression of cancer-related genes expression and are implicated in cancer development and progression (Kafshdooz et al, 2018;Tiwari et al, 2018;Norouzi et al, 2019;Sheervalilou et al, 2020). Previous studies have indicated revealed that the let-7d level is strongly down-regulated downregulated in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play vital roles in regulating the expression of cancer-related genes expression and are implicated in cancer development and progression (Kafshdooz et al, 2018;Tiwari et al, 2018;Norouzi et al, 2019;Sheervalilou et al, 2020). Previous studies have indicated revealed that the let-7d level is strongly down-regulated downregulated in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology has multiple applications with a scientific impact; however, the underlying pathways in interaction of NMs with biological systems at a molecular level still remain to be elucidated. These controversies raise concerns for utilizing nanoscale particles in targeted cancer therapies (Warheit 2010;Setyawati et al 2013b;Sheervalilou et al 2020;Changizi et al 2020;Sheervalilou et al 2021b;Shakeri-Zadeh et al 2020;Sheervalilou et al 2021a;Shirvalilou et al 2021;Kafshdooz et al 2019).…”
Section: Nanotechnologymentioning
confidence: 99%
“…(n = 110). BC, Breast cancer in different cancer biological processes, miRNA studies have become imperative for the detection of miRNA profiles-based prognosis, diagnosis, and theranostics biomarkers (Sheervalilou et al, 2020;Wang et al, 2018). Altered expression of miRNAs provides crucial information about molecular signatures of disease status without the performance of biopsy (Lu et al, 2005;Ayub et al, 2015).…”
Section: Correlation Between Downregulated Mir-140 Expression and Clinical Characteristicsmentioning
confidence: 99%
“…microRNAs (miRNAs/ miRs) are short (about 18-23 nucleotides), conserved, noncoding regulatory RNAs that negatively regulate gene expression based on targeting of the mRNA 3ā€²-untranslated regions (3ā€²-UTR) (Mohammadian et al, 2016b;Norouzi et al, 2019). Computational approaches report that miRNA-mediated the activity of about 30% of all human genomes, in which each miRNA on average potentially RESEARCH ARTICLE miR-140 and miR-196a as Potential Biomarkers in Breast Cancer Patients interact with >100 of mRNA targets (Mohammadian et al, 2016a;Sheervalilou et al, 2020). The biological function of miRNAs as either tumor suppressors or oncogenes related to their target mRNA (Bertoli et al, 2015;Shahabi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%